Legal Awareness of Village Communities Toward the Formulation of Village Regulations (Perdes) Based on Law No. 6 ff 2014 - Valda Pramudita Erviani; Hananto Widodo (Universitas Negeri Surabaya, 2024)
Bendotretek Village is considered by many local people to be that the village's development is still lagging behind compared to the surrounding villages and village officials (individuals) are considered not optimal in disseminating village regulations, as a result many people who do not know about local village regulations. According to Permendagri 111 of 2014 concerning Technical Guidelines for Village Regulations, article 26 which states